Ehrlichiosis in anemic, thrombocytopenic, or tick-infested dogs from a hospital population in South Brazil - Dagnone, Ana Silvia [UNESP]; De Morais, Helio S. Autran; Vidotto, Marilda C.; Jojima, Flavio S.; Vidotto, Odilon (Elsevier, 2003)
Ehrlichia canis has a worldwide distribution, but clinical manifestations may vary geographically. We selected 129 dogs to determine prevalence of ehrlichiosis in dogs with anemia, thrombocytopenia, or ticks presented to a Veterinary Teaching Hospital in South Brazil. Of the 129 dogs, 68 carried the brown dog tick (Rhipicephalus sanguineus), 61 had thrombocytopenia (platelet count <150,000/μl), and 19 had anemia (PCV < 22%). Twenty dogs fulfilled more than one inclusion criteria. Ehrlichiosis was diagnosed by positive amplification of ehrlichial DNA by PCR using primers ECC and ECB that amplify a sequence of the 16S rRNA gene. Presence of E. canis was confirmed by cleavage of the amplified DNA using endonucleases HaeIII and AvaI. Fourteen of 68 (21%) dogs with ticks had ehrlichiosis, whereas 12 of 61 (20%) dogs presented with thrombocytopenia and 4 of 19 (21%) anemic dogs had ehrlichiosis. Similar results were obtained in dogs with thrombocytopenia and anemia (one of eight positive) and in dogs with thrombocytopenia and ticks (two of seven positive). All four dogs with anemia and ticks, and the dog that fulfilled all inclusion criteria yield no amplification of ehrlichial DNA by PCR. Based on our results, one in each five dogs infested by the brown dog tick, with anemia or thrombocytopenia had ehrlichosis. Contrary to widespread believe, ehrlichiosis was not the main cause for thrombocytopenia in our region. © 2003 Elsevier B.V. All rights reserved.
Keywords: Anemia; Ehrlichia canis; Rhipicephalus sanguineus; Thrombocytopenia; bacterial DNA; bacterial enzyme; DNA 16S; endonuclease; ribosome RNA; anemia; animal; animal disease; Brazil; DNA cleavage; dog; dog disease; ehrlichiosis; gene amplification; gene sequence; infestation; isolation and purification; microbiology; nonhuman; polymerase chain reaction; prevalence; thrombocyte count; thrombocytopenia; tick; Animals; DNA, Bacterial; Dog Diseases; Dogs; Ehrlichiosis; Prevalence; Tick Infestations; Ticks; Acari; Canis; Canis familiaris; Ehrlichia; Rhipicephalus